Implementation of STEM Project-Based Learning (PjBL) student worksheet through the â€œotok-otokâ€ boat game on engineering thinking skills - Oktania Putri Angelina; Rifâ€™ati Dina Handayani; Maryani Maryani (Momentum: Physics Education Journal, 2023)
Physics learning is a science learning branch that explores and explains natural phenomena. Nevertheless, students still consider physics learning difficult because it has several abstract concepts and mathematics. Also, physics learning is rarely conducted in terms of higher-order thinking processes. This study aims to investigate studentsâ€™ engineering thinking skills using STEM PjBL on the â€œOtok-Otokâ€ boat game. This type of research is qualitative research with a single case study method. Data were gathered through interviews, observation, and documentation. The data obtained were analyzed using a content analysis method. The results showed that the studentsâ€™ engineering thinking skills were excellent. STEM-PJBL directs students in structuring the engineering thinking skills. Students can solve problems in a structured way, from identifying issues to analyzing alternative solutions to problems. This study is expected as essential information to implement STEM-PJBL for teachers in their physics learning.